The Israeli–Palestinian Separation Wall and the Assemblage Theory: The Case of the Weekly Rosary at the Icon of Our Lady of the Wall - Elisa Farinacci (Journal of Ethnology and Folkloristics, 2017)
In this work I analyse the ethnographic case study of the icon of Our Lady of the Wall as establishing a unique ritual landscape among the cement slabs of the Israeli–Palestinian Wall separating Jerusalem from Bethlehem. Although the Wall has been widely described as a technology of occupation on one side and as a device to ensure security on the other, through Latour’s concept of assemblages I unearth its agency in developing a Christian shrine. Through a decade of weekly recitations of the Rosary along the Wall near Checkpoint 300, the Elizabethan nuns of the Caritas Baby Hospital have been invoking Mary’s help to dismantle the Wall. This weekly ritual represents both political dissent against the bordering action enacted by the Wall, as well as giving visibility to the plea of the Palestinian Christian right to live in this territory in the face of their status as an ethno-religious minority.